Reconciling Differences in Pool-GWAS Between Populations: A Case Study of Female Abdominal Pigmentation in Drosophila melanogaster. Issue 2 (29th December 2015) - Endler, Lukas; Betancourt, Andrea J; Nolte, Viola; Schlötterer, Christian
Abstract: The degree of concordance between populations in the genetic architecture of a given trait is an important issue in medical and evolutionary genetics. Here, we address this problem, using a replicated pooled genome-wide association study approach (Pool-GWAS) to compare the genetic basis of variation in abdominal pigmentation in female European and South African Drosophila melanogaster . We find that, in both the European and the South African flies, variants near the tan and bric-à-brac 1 ( bab1 ) genes are most strongly associated with pigmentation. However, the relative contribution of these loci differs: in the European populations, tan outranks bab1, while the converse is true for the South African flies. Using simulations, we show that this result can be explained parsimoniously, without invoking different causal variants between the populations, by a combination of frequency differences between the two populations and dominance for the causal alleles at the bab1 locus. Our results demonstrate the power of cost-effective, replicated Pool-GWAS to shed light on differences in the genetic architecture of a given trait between populations.